2006
DOI: 10.1161/01.str.0000217418.29609.22
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Blood Flow Threshold of Ischemic Penumbra and Infarct Core in Acute Ischemic Stroke

Abstract: Background and Purpose— Cerebral blood flow (CBF) reduction below critical thresholds discriminates between irreversible infarct core, penumbra, and benign oligemia (penumbra that recovers spontaneously). Thresholds are based on animal studies, and their diagnostic accuracy in humans has never been established. The purpose of this study was to assess the evidence available on CBF thresholds for infarct core and penumbra in adult stroke patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
162
0
11

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(178 citation statements)
references
References 37 publications
(74 reference statements)
5
162
0
11
Order By: Relevance
“…Obviously, further studies are needed to confirm this supposition. 18 Previous studies confirmed that decreased CBV has been shown to be a reasonably reliable marker of the infarct core. The study of Parsons et al 12 found that mean CBV and CTP-SI ASPECTSs are predictive of the final infarct ASPECTS in patients with major reperfusion.…”
Section: Discussionmentioning
confidence: 83%
“…Obviously, further studies are needed to confirm this supposition. 18 Previous studies confirmed that decreased CBV has been shown to be a reasonably reliable marker of the infarct core. The study of Parsons et al 12 found that mean CBV and CTP-SI ASPECTSs are predictive of the final infarct ASPECTS in patients with major reperfusion.…”
Section: Discussionmentioning
confidence: 83%
“…Clinical researchers recognize the need for a consensus in the method used to identify potentially salvageable tissue in stroke patients, as well as the need for consistent thresholds of tissue abnormality (Bandera et al, 2006). Further, the PWI/DWI mismatch method of penumbra determination has yet to be validated in clinical and preclinical stroke research, with no current consensus on perfusion and diffusion thresholds in either research field.…”
Section: Discussionmentioning
confidence: 99%
“…В подобных случаях регистрировались локальные зоны выраженной гипоперфузии преимущественно в области белого вещества и зонах смежного крово-обращения, которые нивелировались усиленным компенсированным кровотоком в корковых обла-стях и бассейнах передней и задней мозговых арте-рий, учитывая умеренную асимметрию полушарно-го кровотока, данная степень перфузионного дефи-цита была наиболее близка к I стадии цереброваску-лярной недостаточности по Барону [12][13][14], однако неоднородность церебральной перфузии в пределах оригинальные статьи пораженного полушария у больных с последствия-ми ишемического инсульта не позволили рассма-тривать ее как вариант компенсации мозгового кро-вотока. В частности, в области белого вещества и зон смежного кровообращения асимметрия средне-го времени транзита крови превышала 80% по срав-нению со здоровым полушарием, со снижением CBF более 40%, что соответствовало пороговым значениям области с повышенным риском развития ишемии [11,15,16]. Большая толерантность белого вещества к ишемии по сравнению с корой головно-го мозга объясняла отсутствие повторных тяжелых ишемических инсультов у пациентов с подобными изменениями церебральной перфузии.…”
Section: Discussionunclassified